Compositional and Material Properties of Rat Bone after Bisphosphonate and/or Strontium Ranelate Drug Treatment - Yuchin Wu; Samer M Adeeb; M. John Duke; David Munoz-Paniagua; Michael R. Doschak (Frontiers Media S.A., 2013)
Purpose. We investigated elemental strontium and/or bisphosphonate drug incorporation upon the compositional and biomechanical properties of vertebral bone, in a rat model of Osteoporosis secondary to ovariectomy. Methods. Six month old female rats were ovariectomized (OVX) and divided into untreated OVX-Vehicle, OVX-RIS (Risedronate bisphosphonate [BP] treated), OVX-SrR (Strontium Ranelate [Protos®] treated), combination OVX-RIS+SrR, and sham-operated controls. After 16 weeks of treatment, rats were euthanized and lumbar vertebra were dissected. Micro-Computed Tomography (micro-CT), Electron Probe Micro-Analysis (EPMA), mechanical testing in compression and nano-indentation testing were then undertaken to evaluate bone morphometry, elemental composition, material properties and strength. Results. Bone Volume was significantly reduced in the OVX-Vehicle (133±10mm3) compared with OVX-RIS (169±22mm3), OVX-SrR (145±2mm3), and OVX-RIS+SrR (172±8mm3). EPMA mapped elemental Sr deposition to the periosteal surface of cortical bone (50-100 µm thick), endosteal trabecular surfaces (20 µm thick), as well as to both vertebral growth plates. The atomic ratios of (Ca+Sr)/P were significantly reduced with SrR treatment (2.4%-6.6%), indicating Sr incorporation into bone mineral. No significant differences were measured in vertebral bone reduced modulus by nano-indentation. Conversely, all BP-dosed groups had significantly increased structural bone strength. Conclusions. Thus, we conclude that BP drugs dominate the conservation of trabecular geometry and structural strength in OP rats, whereas Sr drugs likely influence bone volume and material composition locally. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.